Glyphosate and aminomethylphosphonic acid (AMPA) in urine of children and adolescents in Germany – Human biomonitoring results of the German Environmental Survey 2014–2017 (GerES V). (November 2021) - Lemke, Nora; Murawski, Aline; Schmied-Tobies, Maria I.H.; Rucic, Enrico; Hoppe, Hans-Wolfgang; Conrad, André; Kolossa-Gehring, Marike
Highlights: Population representative internal exposure data on glyphosate and AMPA. All participants had urinary glyphosate levels well below the ADI (0.5 mg/kgbw /day). Quantifiable levels of glyphosate (>LOQ of 0.1 µg/L) found in 50% of the samples. Neither sociodemographic factors nor diet identified as specific source of exposure. Abstract: Since the 1970s, glyphosate has become the most used herbicide of the world. The general population is ubiquitously exposed to glyphosate. Its long-term toxicity, carcinogenic potential and other health effects are controversially discussed. Even though the possible health impacts of glyphosate are of global concern, no population-wide monitoring of glyphosate was done yet. This study presents the worldwide first population-representative data on glyphosate and its metabolite aminomethylphosphonic acid (AMPA) for children and adolescents. 2144 first-morning void urine samples of 3–17-year-old children and adolescents living in Germany were analysed for concentrations of glyphosate and AMPA in the German Environmental Survey for Children and Adolescents 2014–2017 (GerES V). In 52 % of the samples (46 % for AMPA) the urinary glyphosate concentrations were above the limit of quantification of 0.1 µg/L. The geometric mean concentrations were 0.107 µg/L (0.090 µg/gcreatinine ) for glyphosate and 0.100 µg/L (0.085 µg/gcreatinine ) for AMPA. No clear association between exposure to glyphosate or AMPA and vegetarian diet or consumption of cereals, pulses, or vegetables could be identified. The low quantification rate and the 95th percentiles for glyphosate and AMPA of around 0.5 µg/L demonstrate an overall low exposure of the young population in Germany.